Understanding Depression in Daily Practice - Dana Rizki Adilla Sitepu; Deasy Hendrianti; Haznur Ikhwan; Hervina (PT Inovasi Pratama Internasional, 2026)
Depression represents a significant global health challenge, characterized as an abnormal condition arising from an individual's inability to adapt to specific circumstances or events, consequently affecting physical, psychological, and social functioning. According to the American Psychiatric Association (APA, 2013), depressive disorders are classified into two main categories: Major Depressive Disorder (MDD), marked by loss of interest or pleasure in daily activities lasting at least two weeks without manic episodes, and Dysthymic Disorder, a milder but chronic condition persisting for approximately two years. This article employs a comprehensive literature review methodology, systematically examining scholarly journals, scientific articles, websites, and textbooks to explore the characteristics, risk factors, and manifestations of depression across various populations. The findings reveal distinct patterns in specific demographic groups, including pregnant and postpartum women, adolescents, and the elderly, each presenting unique clinical features and predisposing factors. Depression results from a complex interplay of biological, psychological, and social factors, manifesting through characteristic physical, psychological, and social symptoms. The condition often leads to feelings of hopelessness, low self-esteem, persistent pressure, and negative thought patterns that may culminate in suicidal ideation. Early recognition and appropriate intervention are crucial for preventing adverse outcomes across all age groups and populations